Recurrence and progression in non-muscle-invasive bladder cancer using EORTC risk tables - Altieri, Vincenzo Maria; Castellucci, Roberto; Palumbo, Pietro; Verratti, Vittore; Sut, Michal; Olivieri, Raffaella; Manco, Rossella; Ricciardulli, Stefano; Nicolai, Michele; Criniti, Pasquale; Tenaglia, Raffaele Lanfranco (Urologia internationalis, 2012)
It was the aim of this study to evaluate the recurrence and progression at 1, 3 and 5 years in patients with non-muscle-invasive bladder cancer (NMIBC) who underwent a transurethral resection of bladder cancer following intravesical adjuvant chemotherapy or immunotherapy if indicated and to compare them with the European Organization for Research and Treatment of Cancer (EORTC) risk tables. Between 2002 and 2011, a total of 259 patients with NMIBC were treated with transurethral resection of bladder cancer. According to the clinical and pathological factors used by the EORTC scoring system, the patients were divided into four groups, and for each group, the probabilities of recurrence and progression were calculated. The recurrence and progression rates of NMIBC of our patients were similar to those in the EORTC risk score system. Moreover, in our sample group, we found a minimally significant reduction in the recurrence rate in the intermediate- and high-risk groups. From the results obtained, we considered it essential to introduce the use of EORTC risk tables into our clinical practice to determine the recurrence and progression of NMIBC.